The BIG Agent: The Utilization of Embedded Multi-Agent Systems in Unmanned Aerial Vehicles for Autonomous Operations - Santos, Kauã; Costa, Daniel; Lazarin, Nilson; Freitas, Bruno; Pantoja, Carlos (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC); 2025: Anais do XIX Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações, 2025)
Inspired by the high crime rates in Brazil and the use of drones in strategic sectors, this work presents an integration of multi-agent systems (MAS) embedded within unmanned aerial vehicles (UAVs) for autonomous and distributed route operations. The system uses a UAV with two embedded MASs, one of them controlling the drone itself. The other one, dubbed Secretary, is responsible for setting routes for the drone. The approach is validated with a simulation where the drone must visit a predetermined set of points, showing it successfully manages to do so.